The Interpretive Paradigm of Non-financial Aspects in Business Development Analysis (Case Study of Babussalam Al Barokah Dairy Cattle Farm, Bogor Regency) - Canggih Gumanky Farunik; Aryaning Arya Kresna (Budapest International Research and Critics University, 2022)
In the analysis of business development, there are financial and non-financial aspects. Non-financial aspects in the interpretive paradigm can be used to reveal other things that can be concluded from the data found in the analysis. This article seeks to reveal how the role of non-financial aspects can be used as an interpretive paradigm in economics research and other interdisciplinary research. This study uses philosophical research methods with data sources obtained from research by Ginny et al. regarding the potential for developing the Babussalam Al Barokah dairy farming business in Bogor Regency. The result of this research is that the interpretive paradigm can be used to explore the data found in non-financial aspects of business development analysis.